Impact of food additive titanium dioxide on the polyphenol content and antioxidant activity of the apple juice. (15th January 2022) - Li, Qian; Li, Jing; Duan, Mengran; Liu, Lu; Fu, Yinxin; McClements, David Julian; Zhao, Tiantian; Lin, Hongyi; Shi, Jinglan; Chen, Xiaoqiang
Abstract: Food grade titanium dioxide (TiO2 ) usually contains a nanosized fraction, while only a few studies had investigated the effects of TiO2 nanoparticles (NPs) on the other food components via oral exposure. This work investigated the impact of TiO2 NPs on the content, bioaccessibility and antioxidant activity of polyphenols in the apple juice. Results indicated that adding 500 mg/100 g TiO2 NPs significantly decreased the contents of total polyphenol and the main individual polyphenols in the apple juice, which was attributed to the formation of polyphenol-TiO2 NPs charge transfer complexes aggregation. Additionally, the addition of TiO2 NPs reduced the bioaccessibility and antioxidant activity of apple polyphenols in a dose dependent manner. This study indicated that TiO2 NPs can bind polyphenols in the complex food matrix, and provided valuable insights into the influence of food grade TiO2 NPs on the other food components after oral consumption. Graphical abstract: Image 1 Highlights: Effect of TiO2 NPs on the bioaccessibility and antioxidant activity of apple polyphenol was studied. TiO2 NPs can bind with polyphenols in the complex food matrix. TiO2 NPs reduced the contents of total and individual apple polyphenols in a dose-dependent manner. The formation of polyphenol-TiO2 NPs complexes reduced the antioxidant activity of apple juice.